MODEL OF IMPROVING SEAFARERS' COMPETENCE TO REDUCE TURNOVER IN THE MARITIME INDUSTRY - Marsudi, Sugeng; Awwalin, Rodlitul; Supangat; Nasihah, Ainun (Department of Marine Engineering, Universitas Hang Tuah, 2025)
This study aims to develop an effective seafarer competency improvement model in reducing turnover rates in the Indonesian maritime industry. The research method used is a mixed-method with a quantitative and qualitative descriptive approach. Data collection was carried out through questionnaires, interviews, and documentation studies of 150 seafarers from five national shipping companies. The Technology Readiness Level (TRL) of the proposed model was evaluated at TRL 7, indicating that this model has been tested in a limited operational environment with adequate results. The results showed that 65% of seafarers felt they did not receive adequate competency-based training, while 48% of them indicated a desire to change jobs shortly. The competency improvement model, designed based on digital technology and simulation-based training, succeeded in increasing the average competency score of seafarers from 68% to 85% within six months. In addition, the turnover rate of the company that became the pilot project for this model decreased from 22% to 14%. This study offers a state-of-the-art in the form of an integration of competency-based approaches with digital technology, different from previous studies that focused on conventional interventions. The novelty of this study lies in the use of a digital-based model that combines continuous evaluation and adaptive training programs that are tailored to the needs of individual seafarers. This model is expected to be a strategic solution to increase seafarer retention in the maritime industry while strengthening the competitiveness of the Indonesian workforce in the international market.